(untitled) (Global Journal of Human-Social Science, 2023)
This article endorses the deductive method to relate Human Rights and Tax Law, two Law disciplines that appears to be distant, but have a common objective, the protection of the dignity of the human person. The first has the human as its central object of study, currently discussing how to protect it. In turn, Tax Law has the purpose to convert the tax revenues into public policies to protect the fundamental rights of taxpayers. Tax Law seeks to effectively protect Human Rights, alongside with Human Rights towar the same objective: the guarantee of a dignified life for citizens protected by the State.